An Introduction to Many-Valued and Fuzzy Logic : Semantics, Algebras, and Derivation Systems. - Bergmann, Merrie (Cambridge University Press, 2008)
An accessible introduction to many-valued and fuzzy logic designed for undergraduate and graduate students.